Eggs and hatchlings variations in desert locusts: phase related characteristics and starvation tolerance - Maeno, Koutaro O.; Piou, Cyril; Ould Babah, Mohamed A.; Nakamura, Satoshi (Frontiers in Physiology, 2013)
Locusts are grasshopper species that express phase polyphenism: modifying their behavior, morphology, coloration, life history and physiology in response to crowding. Desert locusts, Schistocerca gregaria, epigenetically modify progeny quality and quantity in response to crowding. Gregarious (crowded) females produce larger but fewer progeny than do solitarious (isolated) ones. The variability of progeny quality within single egg pod and the reasons why gregarious progeny have a better survival than solitarious ones remains unclear. This study investigated 1) the effects of rearing density on the variation in egg size within single egg pods 2) the starvation tolerance of hatchlings from mothers with different phases and 3) the physiological differences in hatchling energy reserve. Isolated females produced smaller but more eggs than did crowded ones. The variation in egg size within egg pods was greater in the latter than in the former. A negative relationship between egg size and number of eggs per egg pod was observed for both groups. Under starvation conditions, gregarious hatchlings survived significantly longer than solitarious ones. Among the solitarious hatchlings, the survival time was longer as hatchling body size increased. However, small individuals survived as long as large ones among the gregarious hatchlings. The percentage of water content per fresh body weight was almost equal between the two phases, before and after starvation. In contrast, the percentage of lipid content per dry body weight was significantly higher in gregarious hatchlings than in solitarious ones before starvation, but became almost equal after starvation. These results demonstrated that female locusts not only trade-off to modify their progeny size and number, but also vary progenies’ energy reserves. We hypothesized that gregarious females enhance their fitness by producing progeny differently adapted to high environmental variability and particularly to starvation conditions.